Occlutech percutaneous patent foramen ovale closure: Safety and efficacy registry (OPPOSE). (15th October 2017) - Hildick-Smith, David; Williams, Timothy; MacCarthy, Philip; Melikian, Narbeh; Monaghan, Mark; Spence, Mark; MacDonald, Simon T.; Duke, Abdul; Kovac, Jan; McGregor, Andrew; Hilling-Smith, Roland; Gomes, Arionilson; et al.
Abstract: Introduction: Safety and efficacy data on patent foramen ovale (PFO) closure with the Occlutech Figulla Flex II device are lacking. We undertook a fully monitored prospective Registry on PFO closure using this device. Methods: 100 patients undergoing PFO closure were enrolled into the OPPOSE Registry at 6 UK centres. The primary endpoint was PFO closure (grade 0 or 1 shunt) at 6-month BCTTE assessed by Corelab. Secondary endpoints included implantation success, complications, and atrial fibrillation during follow-up. Results: 100 patients aged 43.8 ± 11.5 years, 53% male, were recruited. Indications for PFO closure included stroke (56%), TIA (29%) systemic embolism (4%) and MI (3%). Closure was undertaken under GA (44%) or LA (56%), with TOE (45%), ICE (31%), no imaging (20%) or TTE (3%). Balloon sizing was used in 98% of cases and showed a tunnel length of 7.3 ± 3.6 mm, primum-secundum separation of 7.0 ± 2.9 mm and basal inlet width of 8.5 ± 3.5 mm. Implantation was successful in all cases using 18 mm (9%), 25 mm (80%), 30 mm (10%) and 35 mm (1%) devices. 5 patients were lost to follow-up. 92 patients underwent six-month BCTTE. The primary endpoint of PFO closure (grade 0 or 1 shunt) at six months was 79.3%. One patient developed major bleeding (BARC 3b), one patient required vascular surgery, and in one patient device embolization was noted at six months and a larger device implanted. There was one case of new atrial fibrillation. Conclusions: This first prospective monitored data for the Occlutech Figulla Flex II device demonstrates good safety and efficacy data at implant and six-month follow-up.